Dilema Nafkah dan Pengasuhan Anak Pasca Perceraian Karena Suami Terpidana (Studi Kasus di Kota Banjarbaru) - Yusna Zaidah; Noor Fitriani; Nadiyah; Erma, Erma Sauva Asvia (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
ABSTRACT Divorce due to a convicted husband is a very complex event and has a significant impact on a woman's life. The husband's status of serving a prison sentence indicates that the ex-wife cannot rely on the ex-husband to fulfill post-divorce obligations, such as alimony or child custody. The focus of this research is on the forms of challenges faced by women after divorce due to their husbands being imprisoned, as well as how these women cope with the challenges of life after divorce because of their convicted husbands. Using a descriptive qualitative method, this study involved six women who divorced because their husbands were imprisoned. The research results show that the challenges faced by women post-divorce due to their husbands being imprisoned include difficulties in meeting family needs, difficulties in providing care and upbringing for children, and a lack of attention from their former husband's relatives. To overcome these challenges, these women took several steps. First, they work outside the home to earn an income to meet their daily needs. Second, they seek help from relatives, especially their own parents and also from their ex-husband's relatives.